2009
DOI: 10.2478/v10007-009-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of matrix controlled transdermal delivery systems of pentazocine: In vitro/in vivo performance

Abstract: Transdermal drug delivery system is being extensively investigated as a viable alternative to drug delivery with improved bioavailability. It offers many advantages over conventional administration such as enhanced efficacy, increased safety, and greater convenience and improved patient compliance. Transdermal route permits the use of a relatively potent drug with minimal risk of systemic toxicity and avoids gastrointestinal degradation and hepatic first-pass metabolism (1-3). A number of therapeutic agents, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…However, the oral administration of PTZ is associated with some drawbacks in terms of poor bioavailability (18-20%), short half-life (2-3 hours) and extensive first pass metabolism that required multiple dosing regimens to maintain the desired therapeutic levels. Interestingly, some of the physicochemical properties of the PTZ, such as Low molecular mass (285.4) and low oral bioavailability, suitable pKa values of 8.5 and 10 and log P of 2.0 make it an ideal candidate to formulate in a novel sustained release DDS such as microsphere which enhanced the therapeutic outcomes of the therapy by using PTZ [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the oral administration of PTZ is associated with some drawbacks in terms of poor bioavailability (18-20%), short half-life (2-3 hours) and extensive first pass metabolism that required multiple dosing regimens to maintain the desired therapeutic levels. Interestingly, some of the physicochemical properties of the PTZ, such as Low molecular mass (285.4) and low oral bioavailability, suitable pKa values of 8.5 and 10 and log P of 2.0 make it an ideal candidate to formulate in a novel sustained release DDS such as microsphere which enhanced the therapeutic outcomes of the therapy by using PTZ [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…No overlapping or merging of spectral peak was observed indicating that there is no interaction between polymer, enhancer and drug. The FTIR drug-excipient compatibility study of matrix-type transdermal patches is extensively reported in the literature (Mukherjee et al 2005 ; Prasad Verma and Chandak 2009 ; Rajabalaya 2010 ; Rajan et al 2009 ; Shinde et al 2008 ; Ubaidulla et al 2007 ). Eudragit RS used as matrix-forming agent is found compatible with most of the drugs (Wade and Weller 1994 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cumulative drug release plots were fitted to the mathematical models for zero-order (r 0 ), first-order (r 1 ) and Higuchi-type (r H ) release kinetics in accordance with the methods of Verma et al [34] and Costa et al [35]. The slopes of the fitted plots were used to estimate the release rates.…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed that when the polymer relaxation rate was similar to that of the diffusion, the anomalous or non-Fickian diffusion pattern of drug release was observed [34]. However, there was reduced deposition of DIM-D within the skin layers observed with increase in polymer concentration, suggesting that there may be other factors playing roles in the permeation of the drug, which is highly lipophilic such as polymer relaxation with time, polymer interaction with the drug and drug permeation with time.…”
Section: Discussionmentioning
confidence: 99%